Superior catalytic action of high-entropy alloy on hydrogen sorption properties of MgH2 - Verma S.K.; Mishra S.S.; Mukhopadhyay N.K.; Yadav T.P. (My University, 2025)
Magnesium hydride (MgH2) is the mostly used material for solid-state hydrogen storage. However, their slow kinetics and highly unfavorable thermodynamics make them unsuitable for the practical applications. The current study describes the unusual catalytic action of a new class of catalyst, a high-entropy alloy (HEA) of Al20Cr16Mn16Fe16Co16Ni16 and its leached version, on the de/re-hydrogenation properties of MgH2. The onset desorption temperature of MgH2 was reduced significantly from 360 °C (for ball-milled MgH2) to 338 °C when it was catalyzed with a leached HEA-based catalyst. On the other hand, a fast de/re-hydrogenation kinetics of MgH2 was observed during the addition of leached HEA-based catalyst. It absorbed ∼6.1 wt% of hydrogen in just 2 min at a temperature of 300 °C under 10 atm hydrogen pressure and desorbed ∼5.4 wt% within 40 min. At moderate temperatures and low pressure, the HEA-based catalyst reduced desorption temperatures and improved re-hydrogenation kinetics. Even after 25 cycles of de/re-hydrogenation, the storage capacity of MgH2 catalyzed with the leached version of HEA degrades negligibly. © 2023 Hydrogen Energy Publications LLC